Metopic Craniosynostosis: A Demographic Analysis Outside an Urban Environment. Issue 3 (May 2016) - Bennett, Katelyn G.; Bickham, Rebecca S.; Robinson, Adina B.; Buchman, Steven R.; Vercler, Christian J.
Abstract : Background: Metopic craniosynostosis has traditionally been cited as the third most common type of isolated synostosis, after sagittal and coronal craniosynostosis. Recently, several urban institutions have observed an increase in the incidence of metopic synostosis. The authors sought to determine if similar demographic changes have occurred in a more suburban setting and if so, what specific variables were associated with this change. Methods: Patients who underwent operative correction of craniosynostosis between 1989 and 2014 were retrospectively reviewed. The type of craniosynostosis as well as sex, family history, birth history, and other demographic data were recorded. Kendall–Mann trend tests and multinomial logistic regressions were conducted, and marginal effects were calculated for all variables included in the model. Results: Records of 493 patients were reviewed. Using Kendall–Mann trend tests, it was determined that metopic, sagittal, and lambdoid craniosynostoses all demonstrated an increase in incidence. Based on raw data, metopic synostosis was found to be the second most common type of craniosynostosis between 2004 and 2014. Male sex and multiple gestations were both associated with metopic craniosynostosis. Conclusions: This study demonstrated an increasing incidence of metopic craniosynostosis over time, which ascended to the second most common type of synostosis in an analysis outside of an urban environment. In our study, male sex and multiple gestation were positively associated with an increased risk of metopic craniosynostosis. Prospective studies are needed to further delineate the evolving characteristics of this patient population.